Role of B‐Type Natriuretic Peptide and N‐Terminal Prohormone BNP as Predictors of Cardiovascular Morbidity and Mortality in Patients With a Recent Coronary Event and Type 2 Diabetes Mellitus. Issue 6 (June 2017) - Wolsk, Emil; Claggett, Brian; Pfeffer, Marc A.; Diaz, Rafael; Dickstein, Kenneth; Gerstein, Hertzel C.; Lawson, Francesca C.; Lewis, Eldrin F.; Maggioni, Aldo P.; McMurray, John J. V.; Probstfield, Jeffrey L.; Riddle, Matthew C.; et al.
Abstract : Background: Natriuretic peptides are recognized as important predictors of cardiovascular events in patients with heart failure, but less is known about their prognostic importance in patients with acute coronary syndrome. We sought to determine whether B‐type natriuretic peptide (BNP) and N‐terminal prohormone B‐type natriuretic peptide (NT‐proBNP) could enhance risk prediction of a broad range of cardiovascular outcomes in patients with acute coronary syndrome and type 2 diabetes mellitus. Methods and Results: Patients with a recent acute coronary syndrome and type 2 diabetes mellitus were prospectively enrolled in the ELIXA trial (n=5525, follow‐up time 26 months). Best risk models were constructed from relevant baseline variables with and without BNP/NT‐proBNP. C statistics, Net Reclassification Index, and Integrated Discrimination Index were analyzed to estimate the value of adding BNP or NT‐proBNP to best risk models. Overall, BNP and NT‐proBNP were the most important predictors of all outcomes examined, irrespective of history of heart failure or any prior cardiovascular disease. BNP significantly improved C statistics when added to risk models for each outcome examined, the strongest increments being in death (0.77–0.82, P <0.001), cardiovascular death (0.77–0.83, P <0.001), and heart failure (0.84–0.87, P <0.001). BNP or NT‐proBNP alone predicted death as well as all other variables combined (0.77 versus 0.77). Conclusions: In patients with a recent acute coronary syndrome and type 2 diabetes mellitus, BNP and NT‐proBNP were powerful predictors of cardiovascular outcomes beyond heart failure and death, ie, were also predictive of MI and stroke. Natriuretic peptides added as much predictive information about death as all other conventional variables combined. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01147250.